Pengaruh Lingkungan Kerja, Gaya Kepemimpinan, dan Stress Kerja Terhadap Kinerja Karyawan PT. Sinar Eka Selaras - Rizky, Hafiz Muhammad; Lestari, Setyani Dwi (MES Bogor, 2025)
This study aims to examine and analyze the influence of work environment, leadership style, and job stress on employee performance at PT. Sinar Eka Selaras. A quantitative approach was employed using a survey method and non-probability purposive sampling technique involving 110 respondents. Data were collected through a Likert-scale questionnaire and analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) approach with the assistance of SmartPLS software. The results show that the work environment significantly contributes to improving employee performance. Leadership style is proven to have a positive influence on employee performance. Job stress, however, does not show a significant effect on performance within this model. Collectively, work environment, leadership style, and job stress simultaneously explain 43.7% of the variance in employee performance, while the remaining 56.3% is influenced by other variables not examined in this study. Leadership style emerges as the most significant factor affecting performance. The work environment also shows a significant effect, although to a more moderate extent compared to leadership style. Job stress, in this study, does not have a direct significant impact on employee performance. These findings enrich the human resource management literature—particularly in the context of the public sector and retail technology—while providing a data-driven basis for corporate policy formulation.